La fluorazione delle acque tra sanità pubblica e diritto pubblico: una valutazione comparata della normativa di alcuni Paesi e delle relative implicazioni di medicina preventiva - Vinceti, Silvio Roberto; Veneri, Federica; Filippini, Tommaso (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Among health professionals and health policymakers concern is growing as to the difficulty of balancing the prevention of dental caries through cost-effective interventions and the need to limit unnecessary exposure of the population, and especially children, to environmental chemicals. In this respect, the use of water fluoridation to prevent tooth decay epitomizes the dilemma by raising questions relevant to both public health and public law, ranging from the balance of public health and medical selfdetermination, the division of powers between local or national authorities over water fluoridation, and the need to avoid the adverse effects of socioeconomic inequalities as well as both under- and over-exposure. Study design. We carried out a narrative review by searching the relevant literature about the laws and rules related to drinking water fluoridation at the community level in the US, UK, and Europe, in order to discuss how the issue is handled from both a public health and public law perspective. Methods. Sources of data for this review were the biomedical and legal literature retrieved by searching online databases, and websites of public health and legal institutions. Results and Conclusions. We found that water fluoridation is still largely adopted throughout the US, while in the UK and particularly in the European Union only a minor part of the population is subject to it. In addition, the recommended and maximum allowed amounts of fluoride in drinking water are being adapted to the public health recommendations and the new regulations, within an evolving evaluation of the epidemiologic evidence and the risk assessment currently in progress by two major regulatory agencies, the US National Toxicology Program - NTP and the European Food Safety Authority - EFSA. Under a comparative public law perspective, the three investigated legislations are facing a reassessment of their policies and regulations, to allow for effective and safe public health measures in the field of water fluoridation and more generally for a preferred use of topical fluoride for caries prevention. A consistent trend across these legislations is the choice to centralize at the national level regulatory and management issues related to water fluoridation, and to carefully balance benefits for dental caries prevention in children and the potential risks of systemic overexposure associated with excess fluoride intake, by promptly responding to the evolving indications by the scientific community and the public health professionals.